Research on Surrounding Rock Control Technology of Dongbaowei Deep Mining Roadway - Chengjia Wu; Tao Qin; Lei Wang; Zhi Liu (Advances in Civil Engineering)
In order to explore the stability control of surrounding rock in the process of deep mining, comparative analysis of stress, deformation, and fracture characteristics of surrounding rock of deep and shallow mining roadway in dongbaotou coal mine, laboratory experiments, field measurement, numerical simulation, and field industrial experiments were adopted to put forward the control plan of the surrounding rock in deep roadway, which were verified by field industrial experiments. The results of laboratory experiments and field experiments show that the mechanical properties of deep roadway surrounding rock of Dongbaowei Coal Mine are significantly lower than those of the shadow roadway, mainly due to the development of joints and fractures of the overlying strata in the deep stope, serious impact on the disturbance of the roadway which has been made by the strong pressure of the stope, and reduced crushing strength of surrounding rock. Through comparative analysis of deep roadway support plan carried out by numerical simulation, the support scheme suitable for Dongbaowei Coal Mine is put forward, which is applied in the field. Field industrial experiments show that after the optimization of support parameters, the deformation of surrounding rock of roadway is well controlled. The displacement of surrounding rock of roadway is basically stable after 10∼15 days. The support of surrounding rock of roadway has good effect, which achieves the goal of stability control of deep roadway surrounding rock.